Cosmetic ingredients from the sea in skin care products - Emeti Ana; Vasiljević Dragana; Primorac Marija; Vuleta Gordana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Sea water, salt and mud have been used for centuries in beautification treatments, but their active ingredients have become a recent challenge in formulating new cosmetic products. Cosmetic ingredients which originate from the sea, are mostly obtained from algae, microalgae, marine sponges, corals and microorganisms. Exopolysaccharides (EPS) are new cosmetic ingredients produced by marine micro-organisms. They are used to protect skin from harmful external influences, give it softness and minimize fine lines. Pseudopterosins, present in the extracts of corals, are used to soothe the skin, while marine sponges are one of the major alternative to animal-derived collagen. Algae have been the most researched group, with the greatest potential among different sources of marine ingredients. Carrageenan, agar, and alginates from algae act as humectants, thickeners and gelling agents. The active ingredients of algae extracts (polysaccharides, proteins, vitamins, minerals) could hydrate, minimize fine lines, protect the skin from UV radiation, decrease redness and cellulite.